Improvement and optimization of slicing algorithm for rapid prototyping manufacturing. (March 2023) - Zhang, Zihua; Zhu, Zhenjiang; Feng, Yongbing; Li, Ran
To overcome the inefficiency of slicing process of rapid prototyping based on STL models, an improved slicing algorithm is proposed. The method builds integral topology of STL models in advance using a Hash table, which enables to get contours directly, and then reduces the search range in slicing by establishing the slicing relation matrix, which can effectively reduce the time cost of slicing. It has been demonstrated that the algorithm has nearly linear time complexity. The method is proved to be effective and efficient through application cases, and the results show better performance than other existing algorithms, especially when the STL model is complex or large.